(3caGjI WGdH GdHjGf aj TQM GdHQgGfs - (3RcQjG Hf jMj Hf jhSa GdTQja GdMSjfjs; (3YHO Gdedc Hf YHO Gddg Hf jhSa Hf eMeO GdLhjfj, CHh GdeYGdj, Qcf GdOjf, GdedbH HEeGe GdMQejf,J (B478 (3g` s
(3ChdgG (B:s
(3GdcdGe ai CaYGd QShd Gddg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3gfG GfJgi GdcdGe ef BNQ GdSaQ GdKGfi ef cJGH caGjI WGdH GdHjGf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B160 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B184s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B- (3GdeZQH (B(35) s
Keywords: (3CUhd Gdabgs